A Web-Based Gaming Approach to Decrease HIV-Related Stigma: Game Development and Mixed Methods Evaluation - Xiaoxiao Zhang; Erman Lai (JMIR Publications, 2022)
BackgroundThe stigma faced by people living with HIV causes difficulties in the treatment of HIV/AIDS. Decreasing this stigma is thus no less urgent than implementing behavioral interventions. Serious games are being increasingly adopted as an intervention mechanism to control HIV/AIDS around the world. However, the development and evaluation of these games in China are far from adequate. ObjectiveThis research aimed to help decrease HIV-related stigma in China via the development and evaluation of a serious game, as well as promote a participatory gamification culture for health interventions. MethodsInitially, a serious game was developed using free resources from a user-generated content website. Then, quantitative and qualitative methods were employed for game evaluation. A randomized controlled trial was conducted to explore the game's effect on HIV-related stigma. The trial included 167 university students, who were randomly allocated to game and control groups. After the experimental evaluation, focus group discussions were held with 64 participants, who were invited to form 16 groups. ResultsThe game was called The Second Kind of Life with HIV (SKLWH), which is a free online game that can be played on computers and smartphones. This game hopes to publicize that people living with HIV can live a normal life, that is, a second life different from that imagined by the public. Based on the gamification practice of SKLWH, the participatory serious game development model (PSGDM) was proposed, which guided the development of 3 other HIV-themed games. The trial showed that intimacy stigma was much more severe than morality stigma and personal interaction stigma. Females were more tolerant of morality stigma than males (mean score: 1.29 vs 1.50; P=.01). The game intervention showed an advantage in decreasing intimacy stigma (mean score [game vs control]: 2.43 vs 2.73; P=.04). The group discussions validated the quantitative results and provided further in-depth information. The game intervention was largely preferred by participants, and the belief in intimacy impossibility was commonly expressed by participants when considering their relationship with people living with HIV. ConclusionsHIV/AIDS education should adopt appropriate media interventions to mitigate different dimensions of HIV-related stigma. Serious games should be used to decrease intimacy stigma, which is the hardest form to diminish. It is expected that the PSGDM can promote the development of more health games. Furthermore, HIV/AIDS intervention requires interdisciplinary efforts and cooperation that will allow more people to participate and share the responsibility of promoting health.